The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1055/s-2007-969059
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of 3-ß-Hydroxy-2,3-dihydrowithanolide F against CCl4-induced Hepatotoxicity

Abstract: Protective effect of 313-hydioxy-2,3-dihydrowithanolide F against CCI4-induced hepatotoxicity has been assessed and the compound was found to possess marked protective effect. A comparison of the protective properties showed that it is more active than hydrocortisone on a weight basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 2 publications
1
28
0
Order By: Relevance
“…The results of our study showed that WC extract administration before ischemia was able to reduce the pycnotic nucleus and widened the perinuclear space in the parietal brain cortex, which is in agreement with the findings of Budhiraja et al that showed cytoprotective effects of WC extract against CCL4-induced hepatotoxicity in rats (28). Another study showed that pretreatment with withania at a dose of 1000 mg/kg significantly improved the neurological deficit in rats (12).…”
Section: Discussionsupporting
confidence: 93%
“…The results of our study showed that WC extract administration before ischemia was able to reduce the pycnotic nucleus and widened the perinuclear space in the parietal brain cortex, which is in agreement with the findings of Budhiraja et al that showed cytoprotective effects of WC extract against CCL4-induced hepatotoxicity in rats (28). Another study showed that pretreatment with withania at a dose of 1000 mg/kg significantly improved the neurological deficit in rats (12).…”
Section: Discussionsupporting
confidence: 93%
“…Hyperglycemia results in the generation of free radicals who can exhaust antioxidant defenses, leading to the disruption of cellular functions, oxidative damage to membranes and enhanced susceptibility to lipid peroxidation. [2,3] Flavonoids are one of the most numerous and widespread groups of phenolics in higher plants. [4][5][6][7][8] Some of them, due to their phenolic structure, are known to be involved in the healing process of free radical-mediated diseases, including diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…The hot aqueous extract of W. coagulans fruits has been shown to exert hepatoprotective, antiinflammatory and antidiabetic effects (5,6). The same hot aqueous extract of W. coagulans fruits has also increased the glucose utilization in isolated rat hemidiaphragm cells (7).…”
Section: Introductionmentioning
confidence: 99%